Analisis Puisi “Lau Annana Lam Naftariq” Karya Farouk Juwaidah - Abdul Latif; Cici Sulista (Institut Agama Islam Negeri Metro, 2019)
Literary was born to reveal the writer’s appreciation for the problems inside, and also as an expression of the writer’s heart situation. Talk about literary certainly have many types, one of them is poetry. Farouk Juwaidah which has been known as king of love nickname because being able to make poetry with beautiful words. One of the poetry is LAU ANNANA LAM NAFTARIQ collect in one of the anthology. The purpose of this reserch to analyze poetry from heuristic and hermeneutic substance in semiotick Riffaterre. Use of this semiotick Riffaterre substance to reveal konotatif meaning in the poetry. The result of this research show that this poetry is an expression of deep sadness because of the separation with the lover, which is caused by the fate of death. So from the separation made him experience fragility of his life so lost of strength in his self to continue a new life. Wishful thinking with the lover disappered like a suddenly dim light. But, behind deep sadness there is positive belief later a new star will appear that illuminate the days.